2007
DOI: 10.1002/pds.1388
|View full text |Cite
|
Sign up to set email alerts
|

Channelling of COX‐2 inhibitors to patients at higher gastrointestinal risk but not at lower cardiovascular risk: the Cox2 inhibitors and tNSAIDs description of users (CADEUS) study

Abstract: The choice of NSAID depended largely on indication and on previous gastrointestinal history, in line with the recommendations of the French health authorities. Possible knowledge of CV risk associated with COX-2 inhibitors did not influence prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
4
27
1
Order By: Relevance
“…5 On the other hand, we show that prescriber response did not select patients different from the patients of nonresponder prescribers, at least for the main study outcomes. 7 Patient representativity in clinical studies is a complex issue. It may be irrelevant in some situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 On the other hand, we show that prescriber response did not select patients different from the patients of nonresponder prescribers, at least for the main study outcomes. 7 Patient representativity in clinical studies is a complex issue. It may be irrelevant in some situations.…”
Section: Discussionmentioning
confidence: 99%
“…Its method and main results have been described in detail elsewhere. 5,7 This study was conducted at the request of the French Health Authorities to examine NSAID user characteristics such as indication of the drug, previous medical history and concomitant prescription of gastroprotective agents.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…Smaller numbers in the subgroups of individual drugs may explain this, but it is possible that differences in prescription habits between The Netherlands and California also play a role. Reimbursement for celecoxib in The Netherlands during 2002 to 2004 was conditional on prescriptions by a rheumatologist 34 35. In addition, it has been suggested that risk of AMI may increase with use of celecoxib in higher doses, which accounts for heterogeneity between studies 18.…”
Section: Discussionmentioning
confidence: 99%
“…The age groups concerned are also quite different, OA patients being usually older, with a mean age of 66 years compared to 55 years for RA, 43 years for common pain. Two-thirds of elderly patients (≥65 years of age) taking tNSAIDs do so for OA (approximately 35%) or back pain (approximately 32%), [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This cohort has already been described [2], as well as the determinants of coxib use, showing that they were used almost exclusively in the patients with rheumatoid arthritis. The main drivers of coxib prescription were age, female gender, previous gastrointestinal history, and previous use of proton pump inhibitors (PPI) [3].…”
Section: Introductionmentioning
confidence: 99%